Idiopathic Pulmonary Fibrosis - Adkins, Jessica M.; Collard, Harold R. (Seminars in Respiratory and Critical Care Medicine, 2012)
Idiopathic pulmonary fibrosis (IPF) is a specific form of progressive, chronic fibrosing interstitial lung disease occurring primarily in older adults and limited to the lungs. The prognosis is dire, with half of all patients progressing to death from respiratory failure within 3 to 5 years from initial diagnosis. The pathogenesis of IPF is complex and incompletely understood, and the natural history of this disease is variable and unpredictable. There is no widely accepted treatment for IPF, except for lung transplantation. Nevertheless, these are important and exciting times for the diagnosis and management of patients with IPF. Novel diagnostic approaches (e.g., biomarker-based), improved prognostic models, and clinical trials of novel drug agents may alter disease management substantially over the next few years. For now, clinicians should practice comprehensive management, including symptom-based management, aggressive management of comorbidities, and patient education and support.
Keywords: idiopathic pulmonary fibrosis; usual interstitial pneumonia; familial interstitial pneumonia